N, N, N′, N′‐Tetrabromobenzene‐1, 3‐disulfonamide and Poly(N‐bromo‐N‐ethylbenzene‐1, 3‐disulfonamide) as Mild and Efficient Catalysts for Solvent‐free Synthesis of N‐Cyclohexyl‐2‐aryl(alkyl)‐imidazo[1, 2‐a]pyridin‐3‐amine Derivatives. (1st May 2014) - Ghorbani‐Vaghei, Ramin; Amiri, Mostafa
<x xml:space="preserve">Abstract</x> N‐Cyclohexyl‐2‐aryl(alkyl)‐imidazo[1, 2‐a]pyridin‐3‐amine derivatives have been synthesized in good to high yields from o‐aminopyridine, aromatic and aliphatic aldehydes, and cyclohexyl isocyanide in the presence of N, N, N′, N′‐tetrabromobenzene‐1, 3‐disulfonamide and poly(N‐bromo‐N‐ethylbenzene‐1, 3‐disulfonamide) as catalysts, at room temperature under solvent‐free conditions.